Total Quality Management: Paradigma Baru Managemen Perguruan Tinggi dalam Menghadapi Persaingan Kualitas Pendidikan - Wariyanti (UHN IGB Sugriwa Denpasar, 2017)
College is one of the means to build community. Universities can also be regarded as the agent of change in society and even the world. Humans were expected today are capable of developing their potential throughout. Overview whole human beings has been defined in the law No. 20 of 2003 on the System Pendidian National Article 3 which states that the National Education aims at developing students' potentials in order to become a man of faith and fear of God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and become citizens of a democratic and accountable. Based on these conditions, a University is a public institution undertaking the community to help to create students who have the expected quality. With the demands of current conditions it is necessary seoramg leaders and members who have high performance in managing and running the educational process. While universities are expected are universities which have members who are always learning to achieve a change for the better in serving the community.